Influence of Well-Being Indices and Recovery State on the Technical and Physiological Aspects of Play During Small-Sided Games. Issue 10 (October 2021) - Selmi, Okba; Gonçalves, Bruno; Ouergui, Ibrahim; Levitt, Danielle E.; Sampaio, Jaime; Bouassida, Anissa
Abstract : Abstract: Selmi, O, Gonçalves, B, Levitt, DE, Ouergui, I, Sampaio, J, and Bouassida, A. Influence of well-being indices and recovery state on the technical and physiological aspects of play during small-sided games. J Strength Cond Res 35(10): 2802–2809, 2021—Soccer players performing at high level are frequently exposed to periods of intense training, which can induce substantial stress and fatigue. These high-intensity stimuli likely lead to a lower state of well-being and poor recovery and, consequently, may affect players' performance. This study aimed to assess the influence of well-being indices (i.e., self-ratings of sleep, stress, fatigue, and delayed onset muscle soreness [DOMS]) and the total quality of recovery (TQR) on technical and physiological measures during soccer small-sided games (SSGs). Twenty male professional soccer players (age: 25.1 ± 1.0 years) performed four 25-minute SSG sessions. Well-being indices were collected before each SSG-session. Heart rate was continuously measured throughout each session, and the ratings of perceived exertion and blood lactate concentration were collected after each SSG. A hierarchical cluster analysis was performed across variables and cases to identify associations between variables and variability in players' responses between sessions. No significant correlations were found between well-being indices, TQR and physiological parameters. Total quality recovery was positively correlated with successful pass % ( r = 0.27) and interceptions ( r = 0.25) and negatively correlated with lost balls ( r = −0.25). Fatigue and DOMS were negatively correlated with tackles ( r = −0.29, r = −0.28, respectively), successful pass % ( r = −0.58, r = −0.55, respectively) and interceptions ( r = −0.25, r = −0.27, respectively), and positively correlated with lost balls ( r = 0.32, r = 0.28, respectively). Results provide an alternative and complementary method to understand training responses and can be an objective tool to help create subgroups in training for optimizing performance. This study demonstrates the efficacy and utility of using simple well-being and recovery measures to help coaches monitor athlete readiness.